KERJASAMA NIGERIA-INDONESIA DALAM BIDANG INVESTASI MAKANAN TAHUN 2008-2014 - Sri Kurnia Fitri Ningsih; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research is intended to explain cooperation between nigeria with Indonesia in the field of food investment. In the cooperation many Indonesian companies that invest in Nigeria. This research will discuss what the purpose of nigeria cooperation with Indonesia in the field of food investment.As for the method used in the study is qualitative research metodhs with explanation analysis methods. Data collection techniques are used library research techniques which utilizes secondary data obtained through library were abstracted from the literature such as books, journals, reports, documents, and other materials that support this research. The writer uses neoliberalism perspective and nation state level analysis. Theory used in this research is theory of international cooperation by K.J Holsti and used used investment concept.This research find out that Nigeria in collaboration with Indonesia in the field of food investment because Nigeria want to improve the food industry in Nigeria. Growth in the industrial sector in Nigeria has a very large, it is seen with a contribution of 43% of the total GDP of Nigeria in 2012. The significant support of the Nigerian government in the industrial sector is also a major trigger industrial development in Nigeria which is fast enough with Nigeria government policy issued in the food industry to support the development of the food industry.Keywords: Cooperation, Food Investment, Food Industry, Government Policy